Influence of the Quality System and Technological Innovation in the Results Focused on Continuous Improvement in the manufacture of Distribution and Power transformers - Ramos Carrión, Jorge Carmelo (2018)
This article presents the results of an applied research of an explanatory type, whose objective was to analyze and determine the influence of the management of the quality system and technological innovation in the results focused on the continuous improvement in the manufacture of transformers distribution and power. The sample in study was constituted by the personnel of companies manufacturers of the sector, located in Metropolitan Lima. The methodology developed was able to determine the level of impact using a multiple linear regression model.